2005
DOI: 10.1074/jbc.m413884200
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Mutational Analysis of Trypanosoma brucei Prostaglandin H2 Reductase Provides Insight into the Catalytic Mechanism of Aldo-ketoreductases

Abstract: Trypanosoma brucei prostaglandin F 2␣ synthase is an aldo-ketoreductase that catalyzes the reduction of prostaglandin H 2 to PGF 2␣ in addition to that of 9,10-phenanthrenequinone. We report the crystal structure of TbPGFS⅐NADP protonation through a water molecule, while exerting an electrostatic repulsion against His 110 that maintains the spatial arrangement which allows the formation of a hydrogen bond between His 110 and C 11 carbonyl of PGH 2 . We also show that Tyr 52 acts as the general acid catalyst fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 50 publications
0
30
0
Order By: Relevance
“…Furthermore, a catalytic role of His-110 could not be entirely excluded. Quantum mechanical calculations of the energetics of reaction pathway (Lee et al, 1998) support a primary role of His-110 in AKR1B catalysis and in recent analysis of AKR5A2 catalysis, Kilunga et al (Kilunga et al, 2005), found that of the 4 residues of the catalytic tetrad, only His-110 and Lys-77 are important for the reduction of PGH 2 to PGF 2α , and that active site tyrosine and aspartate were not required. Active site tyrosine was, however, required for the reduction of the non-physiological substrate 9,10-phenanthroquinone.…”
Section: B) Catalytic Properties Of Akrsmentioning
confidence: 99%
“…Furthermore, a catalytic role of His-110 could not be entirely excluded. Quantum mechanical calculations of the energetics of reaction pathway (Lee et al, 1998) support a primary role of His-110 in AKR1B catalysis and in recent analysis of AKR5A2 catalysis, Kilunga et al (Kilunga et al, 2005), found that of the 4 residues of the catalytic tetrad, only His-110 and Lys-77 are important for the reduction of PGH 2 to PGF 2α , and that active site tyrosine and aspartate were not required. Active site tyrosine was, however, required for the reduction of the non-physiological substrate 9,10-phenanthroquinone.…”
Section: B) Catalytic Properties Of Akrsmentioning
confidence: 99%
“…It is hypothesized that ablation of a signal or induction of an inappropriate signal will be lethal to these cells. From past experiments it is clear that trypanosomes have the potential to propagate signals involving Ca 2ϩ , cyclic nucleotides, eicosenoic acid, and phosphoryl transfer (1)(2)(3)(4). However, in stark contrast with mammalian cells, where complex interacting signal networks have been described, a simple signal pathway has yet to be identified in Trypanosoma brucei.…”
mentioning
confidence: 99%
“…However in T. brucei three ALRs have been reported. One of the aldo-keto reductase from T. brucei has a known three-dimensional structure (Kilunga et al, 2005). A sequence analysis was performed with the ALR sequences of Leishmania, T. brucei sequence with known structure along with the experimentally characterized aldose reductase sequences from human, yeast and other known aldose reductase sequences.…”
Section: Relationship Of Ldalr To Other Members Of the Aldose-keto Rementioning
confidence: 99%
“…The modeling has been based on the available (2.1 Å) crystal structure of T. brucei brucei Prostaglandin-F-synthase (TbPGFS) structure (Kilunga et al, 2005) which is identified as the closest homologue of LdALR of known 3-D structure. The best sequence identity between T. brucei homologue and LdALR is 61%.…”
Section: Comparative Modeling Of L Donovani Aldose Reductasementioning
confidence: 99%